Trans-triquetral Perilunate fracture dislocation. (April 2018) - Rhind, John-Henry; Gulihar, Abhinav; Smith, Andrew
Abstract: Perilunate dislocations and perilunate fracture dislocations are rare and serious injuries. Perilunate dislocations represent less than 10% of all carpal injuries of which 61% represent transcaphoid fractures. Because of their rarity, up to 25% of perilunate dislocations are initially missed on first assessment. We present the case of a 66-year-old-gentleman who sustained an isolated trans-triquetral perilunate fracture dislocation while walking his dog. This was diagnosed in the emergency department and he underwent open reduction internal fixation after failed attempts at closed reduction in the ED and in theatre under general anaesthesia. After further removal of his Kirschner wires and physiotherapy he is noted to have had a successful outcome with his treatment at 9 months follow up post operatively. We found that this is the first case of it's kind reported in the literature highlighting the rarity of this injury pattern.